2021
DOI: 10.1186/s12886-020-01763-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between myopia and parental myopia and outdoor time among students in Wenzhou: a 2.5-year longitudinal cohort study

Abstract: Background To evaluate the impact of parental myopia and outdoor time on myopia among students in Wenzhou. Methods We examined 1388 primary students from first grade to third grade in Wenzhou from September 2012 to March 2015. We performed noncycloplegic refractometry on each student every six months and axial length (AL) measurements every year. At the commencement of our study, children were asked to complete a questionnaire regarding near work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
(49 reference statements)
3
13
0
Order By: Relevance
“…In our results, a relationship was found between the presence of myopia in one or both parents and the refractive state of the children. Similar results were found in the study by Jiang et al [ 41 ]: according to the number of myopic parents, the risk of the child having myopia can be predicted.…”
Section: Discussionsupporting
confidence: 90%
“…In our results, a relationship was found between the presence of myopia in one or both parents and the refractive state of the children. Similar results were found in the study by Jiang et al [ 41 ]: according to the number of myopic parents, the risk of the child having myopia can be predicted.…”
Section: Discussionsupporting
confidence: 90%
“…Whether close work is related to myopia is still controversial. Jiang et al [24] conducted a 2.5-year longitudinal cohort study on primary students from first grade to third grade in Wenzhou, China, and found that close work had no effect on myopia. However, the current study reported the effects and possible interactions of near work and outdoor activity on myopia among Chinese high school students in Nantong, China, and found that the risk of myopia was significantly increased after more than 2 h of homework a day.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents, sports such as basketball, volleyball, and badminton can effectively reduce the risk of becoming myopic [14]. Factors such as more outdoor activities, exposure to natural light, and outdoor environment are protective for the eyes of adolescents [15][16][17][18]. Through binary logistic regression analysis, it is found that regular physical activities, daily time spent on in-school physical activities, after-school physical activities, eye exercises, and attitude towards physical education are the main influencing factors in the prevention of myopia.…”
Section: Discussionmentioning
confidence: 99%